THE INFLUENCE of PARENTS on ADOLESCENT SEX BEHAVIOR - Apriani, Astuti; Anjarwati, Anjarwati (LPPM Universitas Prima Nusantara Bukittinggi, 2020)
Background: adolescence is a period of time of sexual health development including the development of sexual identity, self-esteem, sexual responsibility. For some teens, it is also a period of time of sexual initiation, pressure to begin sexual activity and sexual experimentation. The result of research in North Western Ethiopia stated that almost 1/5 from 157 (19%) of teenager has reported that they already have pre-marital sexual relation, where 91 (22,7%) are male and 66 (15,5%) are female. The average age in the first sexual relation is 16,48 (1,59) for male and 15,89 (1,68) for female. Based on data, it can be explained that more than 3?4 teenagers who are active sexually has involved in pre-marital sexual relation before having their 18th birthday. Lack of parental supervision is one of the factors that adolescents engage in risky sexual behavior so that adolescents spend more time with close friends and peers compared to parents. Method: Apprasial studies program using Critical Appraisal Skills Program (CASP) and methods of synthesis using a modification PICO data sources obtained from PubMed with year period of 2009 – 2019. Results: Parents are one of the factors most related to adolescent behavior. This is due to the lack of attention, communication and monitoring by parents in adolescents causing teenagers to spend more life with their peers, such as at school or other activities outside of school. More teenage time is spent with peers than with parents resulting in more adolescents being exposed to the environment outside their parents and family. Conclusion: High quality relationships with parents can reduce the likelihood of intention to have sexual relations in adolescence and good communication with parents about sex also reduces the influence and pressure from peers who are sexually related. Lacking religion and lack of closeness with parents are also triggers for adolescents having early sexual relations.